The measurement of sustainability disclosure: Abundance versus occurrence - Joseph, Corina; Taplin, Ross (Elsevier, 2011)
Content analysis (disclosure abundance) and disclosure indices (disclosure occurrence) are popular methods for measuring the extent of disclosure. Few studies however compare the two approaches empirically or use empirical evidence to justify the use of one approach over the other. A study of sustainability reporting on Malaysian local government websites is used to illustrate how these two measurement approaches lead to different concepts of the extent of disclosure. Furthermore, hypothesised relationships between disclosure and independent variables based on theory differ substantially depending on the measurement approach for disclosure. Recommendations for the measurement of disclosure are suggested.